Use of Hybrid Flame Retardants in Chemically Foamed rPET Blends - Veronika Anna Szabó; Sándor Kálmán Jakab; András Kovács; Tamara Zsuzsanna Böcz; Gábor Dogossy (Crystals)
The foamed structure of recycled polyethylene-terephthalate (rPET) is a promising solution for industrial applications; however, the remedy for its inherent melt-dripping property is still a challenging topic. In our research, we were able to improve the flame retardancy of the endothermic–exothermic hybrid rPET foam by adding a different mixture of flame retardants to the formula. Three different kinds of halogen-free flame retardant agents were used: ammonium polyphosphate-based Exolit AP 422 (AP), organic aluminum phosphate in the form of Exolit OP 1240 (OP), and Budit 342 containing melamine polyphosphate (MPP). The hybrid flame retardant mixture, by combining the swelling and charring mechanism, increased the flame retardancy of the samples. The sample made with 15 phr OP and 5 phr MPP displayed outstanding performance, where five samples were capable of self-extinguishing in 5 s, while only slightly decreasing the tensile and flexural strength properties and simultaneously increasing the Young and flexural modulus compared to the reference sample. The addition of MPP reduced the porosity in many cases, while preventing cell coalescence. Our results prove that the hybrid flame retardant agent frameworks efficiently increase the flame retardancy of rPET foams, facilitating their application in industrial sectors such as the aerospace, packaging, renewable energy, and automotive industries to realize sustainability goals. The utilization of halogen-free flame retardants is beneficial for better air quality, reducing toxic gas and smoke emissions.